Development of quality management system in accordance with ISO 9001:2000 for Ben Thanh tourist - Hanoi : Luận văn ThS. Kinh doanh và quản lý: 60.34.05 - Nguyen, The Cuong (Đại học Quốc gia Hà Nội, 2017)
81 p. + CD-ROM